Accounting measurement and disclosure for social responsibility and its impact on the quality of financial reports Statistical study on the farm markets company in Jeddah - Kingdom of Saudi Arabia - ezdini, sihem hamda; bdullah Al-Otaibi, Jawahir Atiq A (Journal of Research in Finance and Accounting, 2020)
Accountability for social responsibility is the result of the need and is one of the most recent stages of development in accounting thought emerged as a reaction to the importance of the role that companies play, so the survival of the enterprise has become linked to its social responsibility towards society. One of the most important matters related to social responsibility is the measurement and disclosure of social information in financial reports. The importance of measurement and disclosure is evident in increasing the degree of public confidence and gaining a good reputation for the facility, which leads to ensuring continuity. One of the main goals of social responsibility accounting is to provide information and prepare social reports that would reflect the extent of the business organizations ’commitment to disclose their social performance to provide a sufficient amount of useful information in making rational decisions in various parties.